Neurobiology of acupuncture - Zeng, Bai-Yun; Zhao, Kaicun; Liang, Fan-rong (International review of neurobiology ;, 2013)
This book summarises the recent development in acupuncture research and in particular, the neurobiology of acupuncture. It provides a focus but a diverse range of subjects covering many body systems. The first a few chapters discuss the basic principles of acupuncture, then its modulatory effects on nervous system such as induction of neurotrophin and neurogenesis in the brain. Late chapters explore the clinical effects and potential mechanisms of acupuncture on different conditions ranging from neurological diseases such as Parkinson's, Alzheimer's, and stroke, to psychiatric illnesses, insomnia, hypertension, gastrointestinal diseases and drug addiction. We believe this will promote the understanding acupuncture treatment and enhance acupuncture research in the future. This volume of International Review of Neurobiology brings together cutting-edge research on the neurobiology of acupuncture. It reviews current knowledge and understanding, provides a starting point for researchers and practitioners entering the field, and builds a platform for further research and discovery.